A systematic review of site-selection procedures of PV and CSP technologies - Sofia Spyridonidou; Dimitra G. Vagiona (Energy Reports, 2023)
Solar energy is one of the leading renewable energy sources in terms of installed power capacity on a global scale. Scientific research on the site-selection procedures of solar photovoltaics (PV) and concentrated solar power (CSP) technologies is of significant importance, contributing to environmentally sustainable, technically and economically viable, and socially acceptable solar energy projects. This systematic review provides direct analysis and assessment of existing site-selection procedures and addresses a gap in knowledge in the solar energy research. Among a total of 10,121 scientific studies filtered and investigated, a total of 152 scientific studies were identified as eligible and reviewed in detail. Each selected study was further investigated through 11 key thematic modules: (1) site-selection methodologies; (2) type, number, and exclusion limits of exclusion criteria; (3) type, number, importance, priority, and suitability classes of assessment criteria; (4) optimization modules and criteria; (5) studies’ geographic locations; (6) spatial planning or reference scales; (7) solar radiation data estimation and analysis; (8) sensitivity analysis related to site-selection procedure; (9) participatory planning approaches, groups, and contributions; (10) laws, regulations, and policies related to site-selection procedure; (11) suitability indexes (linguistic or/and numeric) and ranking procedures. Important insights and useful data trends are identified and highlighted in these key thematic modules of site-selection issue, enhancing future studies and globally improving siting implementations.